Quantitative assessment of the power loss of silicon PV modules by IR thermography and its dependence on data-filtering criteria - Teubner, Janine; Buerhop, Claudia; Pickel, Tobias; Hauch, Jens; Camus, Christian; Brabec, Christoph (Progress in Photovoltaics, 2019)
Reliability and quality control of photovoltaic (PV) plants increases in importance as the relevance of PV for the worldwide renewable energy production grows. In this study, a new method is presented which allows for a quantitative assessment of silicon PV module performance solely by relying on the cell temperatures measured via thermography (IR). A module temperature and power key figure are formulated and found to correlate very well with a linear relationship. The dependence of the deduced correlation's precision on measurement conditions is calculated and discussed. It facilitates decision-making because optimal measurement conditions usually occur only very rarely, such that a compromise between data quality and measurement frequency has to be found. The power loss correlation presented in this paper may be used as part of a maintenance routine in order to ensure the best possible long-term performance of the PV plant over its lifetime. The practical application in the field is outlined and explained.
CRIS-Team Scopus Importer:2019-08-23
Keywords: empirical power correlation; infrared measurement; PV; silicon modules; UAV